Dual‐loop control strategy applied to the cluster of multiple nanogrids for rural electrification applications. Issue 3 (24th July 2019) - Nasir, Mashood; Anees, Muhammad; Abbas Khan, Hassan; Guerrero, Josep M.
Abstract : In this study, a dual‐loop control strategy is applied to a highly distributed architecture of photovoltaic/battery‐based DC microgrid built through an interconnection of a cluster of multiple nanogrids. Typically, in these distributed architectures, resource sharing among the spatially distributed nanogrids is enabled via communication‐based control methodologies, which adds cost and complexity to the overall system. Alternately, a communication‐less and decentralised control methodology is proposed which utilises inner loop current control and outer loop voltage droop ( V–I droop) control for the coordinated resource sharing among the distributed resources. The proposed control scheme adapts various modes based on the local measurements of bus voltage and battery state of charge, therefore, offers a distributed solution, omitting the need for centralised communication control. Various scenarios of power sharing among the contributing nanogrids are evaluated through the proposed multi‐mode adaptive control. The efficacy of the proposed control scheme is validated through simulations on MATLAB/Simulink and laboratory scale hardware prototype. Results show that the proposed decentralised control strategy is capable to ensure stable and coordinated operation without any dedicated layer of communication among the dispersed generation/storage resources.